Multifactorial approaches for interaction studies between Pacific oyster Crassostrea gigas and two virulent Vibrio, V. splendidus and V. aestuarianus : epidemiology, variable host susceptibility and pathogenesis - De Decker, Sophie (HAL CCSD, 2010)
Oyster production is the main aquaculture activity in France and is dominated by the rearing of Crassostrea gigas. In the aquatic ecosystems where the species is grown, bacteria of the genus Vibrio are found to be dominant. Two Vibrio species, V. splendidus and V. aestuarianus, are frequently associated with Crassostrea gigas summer mortality episodes. The aims of this work were to study Vibrio-oyster interactions and their modulations according to virulence mechanisms and to genetic and physiological parameters of the host. Using specific, sensitive and quantifying diagnostic tools developed in this study, as well as standardized experimental infection trials, some components of the virulence of Vibrio strains and host susceptibility were delineated and the dynamics of Vibrio infection characterized through pathogenesis studies.The study of the specific diversity of bacterial strains isolated during summer mortality events, on broad temporal and spatial scales, revealed an epidemiological association of the group V. splendidus and the species V. aestuarianus. Because a correlation has been observed between pathogenicity and metalloprotease activity, a predictive phenotypic test of virulence was developed. Exploration of the synergy phenomenon between the pathogenicity of the two strains observed in experimental co-injection led to the characterisation of a system of quorum sensing controlling the production and transcriptional expression of the gene encoding metalloprotease Vsm and Vam at the intraspecific (V. splendidus) and interspecific level (V. splendidus/V. aestuarianus).The statistical analysis of mortality kinetics in half-sib diploid and triploid families subjected to experimental vibriosis by co-infection revealed an increased susceptibility of oysters during the period of active gametogenesis. The triploid oysters subjected to this same experimental infection did not show any significant advantage. The existence of a genetic basis for oyster susceptibility to experimental vibriosis was illustrated by ...